2019
DOI: 10.3389/fonc.2019.00497
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Risk Factors of Pathologic Complete Response Following Neoadjuvant Chemoradiotherapy for Rectal Cancer: A Population-Based Analysis

Abstract: Background: Patients with rectal cancer who achieve pathologic complete response (pCR) after neoadjuvant chemoradiotherapy (nCRT) may have a better prognosis and may be eligible for non-operative management. The aim of this research was to identify variables for predicting pCR in rectal cancer patients after nCRT and to define clinical risk factors for poor outcome after pCR to nCRT and radical resection in rectal cancer patients. Methods: A retrospective review was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 57 publications
3
47
0
Order By: Relevance
“…The material is not large enough to draw firm conclusions from, and it is also retrospectively collected. Nonetheless, similar results were seen in other studies investigating factors associated with pCR after preoperative CRT [13,19,21] or scRT [36]. Tumors in stage cT2 also constitute most patients with CR after CRT [37].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The material is not large enough to draw firm conclusions from, and it is also retrospectively collected. Nonetheless, similar results were seen in other studies investigating factors associated with pCR after preoperative CRT [13,19,21] or scRT [36]. Tumors in stage cT2 also constitute most patients with CR after CRT [37].…”
Section: Discussionsupporting
confidence: 88%
“…However, in the groups receiving scRT+CT as many as 26% of the mucinous tumors had a CR (13 of 50 patients). This was not expected, as previous studies have indicated that rectal tumors with mucus production have poor response to CRT [20,21,35,48]. Too few patients are included in our study to be able to make firm conclusions, but if true, mucinous tumors could also reach pCR and should thus not be excluded from organ preservation, unless RT is given alone.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…A series of studies has confirmed the predictive ability of serum carcinoembryonic antigen (CEA) in pathological complete response (pCR). [8][9][10] In a study by Song et al, carbohydrate antigen 19-9 (CA19-9) appeared to predict downstaging to stage 0-I. 11 Even indices from the complete blood count, such as the platelet-lymphocyte ratio, have been shown to predict pCR.…”
Section: Introductionmentioning
confidence: 99%